Effect of management practices on rooting pattern of Dalbergia sissoo under agri-silvicultural system - NEWAJ, RAM; SOLANKI, K R; AJIT, AJIT; HANDA, A K (The Indian Journal of Agricultural Sciences, 2014)
A field study was initiated at Jhansi during 1994 on different root management practices (deep ploughing, root barrier-polythene sheet, deep basin, pruning up to 40% height and control) on rooting pattern of Dalbergia sissoo Raxb. under agri-silvicultural system. Among all the root management practices, deep ploughing and deep basin exhibited significantly lower root density at different places (0.5, 1.0, 2.0 and 3.0 m) from tree base compared with the pruning, root barrier and control. Specific root length shows a similar trend at different distances (0.5, 1.0, 2.0 and 3.0 m) from tree base. In general, the specific root lenght was lower in 15 cm-topsoil layer near by the tree base and it increased sharply with increase of distances from tree base in all the management practices. The value of specific root length was higher in deep basin and deep ploughing at all the places from tree base. Root biomass in upper 15 cm soil layer under deep basin was significantly lowest at 0.5, 1.0, 0.0 and 3.0 m away from tree base compared with deep ploughing, pruning, root barrier and contral.